A multi-channel near-infrared spectroscopy study of prefrontal cortex activation during working memory task in major depressive disorder - Pu, Shenghong; Yamada, Takeshi; Yokoyama, Katsutoshi; Matsumura, Hiroshi; Kobayashi, Hokuto; Sasaki, Natsuko; Mitani, Hideaki; Adachi, Akiko; Kaneko, Koichi; Nakagome, Kazuyuki (Neuroscience research, 2011)
▶ We study prefrontal hemodynamic response to working memory processing in patients with depression. ▶ Hemodynamic response was measured using near-infrared spectroscopy. ▶ Patients with depression show hypofrontality and poorer task performance than normal controls. ▶ Hyper- or hypofrontality in depression depends on the cognitive demand of the task adopted. Many neuropsychological studies demonstrate impairment of working memory in patients with major depressive disorder (MDD). However, there are not enough functional neuroimaging studies of MDD patients seeking for the underlying brain activity relevant to working memory function. The objective of this study is to evaluate prefrontal hemodynamic response related to working memory function in patients with MDD. Twenty-four subjects with MDD and 26 age- and gender-matched healthy subjects were recruited for the present study. We measured hemoglobin concentration changes in the prefrontal and superior temporal cortical surface areas during the execution of working memory task (WM; 2-back, letter version) using 52-channel near-infrared spectroscopy (NIRS), which enables real-time monitoring of task-related changes in cerebral blood volumes in the cortical surface areas. MDD patients showed a smaller increase in lateral prefrontal and superior temporal cortex activation during the 2-back task and associated poorer task performance than healthy controls. The results coincided with previous findings in terms of working memory deficits and prefrontal cortex dysfunction in MDD patients, but contradicted with some previous fMRI studies that suggested increased cortical activity during the working memory task in patients with depression. The contradiction may, in part, be explained by a relatively low level of cognitive demand imposed on the subjects in the present study.